ҚАРАҚАЛПАҚСТАН РЕСПУБЛИКАСЫ МӘДЕНИЙ ӨСИМЛИКЛЕРИНИҢ ЖАБАЙЫ ТУҚЫМЛАСЛАРЫНЫҢ ТҮРЛИК ҚУРАМЫН ҮЙРЕНИЎ - Ажиев, А.Б.; Альменова, Г. (ILIM hám JÁMIYET, 2019)
The author of the article analyzes the species composition and the degree of perspective of wild relatives of cultivated plants of the flora of the Republic of Karakalpakstan. In the result of processing of literary data and field research, the list of wild relatives of cultivated plants of the flora of Karakalpakstan comprised 171 species from 116 genera and 38 families. The greatest species diversity is found in the Amudarya delta. The most common are representatives of this family. Chenopodiaceae, Fabaceae and Poaceae. The wild relatives of cultivated plants with feed, nutritional and medicinal properties predominate in the economically valuable groups.